2023
DOI: 10.21203/rs.3.rs-2517316/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between hematological parameters and bronchopulmonary dysplasia in premature infants

Abstract: AIM To evaluate the association between hematological parameters on the first day and bronchopulmonary dysplasia (BPD) in preterm infants and to help with early warning, identification, and intervention in the development of BPD. METHODS This is a retrospective study of all premature infants admitted to neonatal intensive care From January 2017 to June 2022, BPD was diagnosed as hypoxia exposure over 28 days, and levels of neutrophil-to-lymphocyte ratio(NLR), platelet-to-lymphocyte ratio༈PLR༉, Platelet count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Previous research has identi ed SIRI as a potential biomarker for predicting BPD [34] . PMI re ects the body's in ammatory and immune statuses [33] , consistent with Sati research [35] .…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has identi ed SIRI as a potential biomarker for predicting BPD [34] . PMI re ects the body's in ammatory and immune statuses [33] , consistent with Sati research [35] .…”
Section: Discussionsupporting
confidence: 84%
“…Previous research indicated that Many biomarkers, such as CRP, and PCT, could be used in the auxiliary diagnosis of sepsis, but their serum levels may be affected by many other stimulations other than infection. [22][23][24] therefore, compared with HDL and LDL, their predictive abilities appeared low. That's consistent with our research.…”
Section: Discussionmentioning
confidence: 95%